2020
DOI: 10.1002/sctm.19-0323
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of germinal zone neural stem cells from the cerebrospinal fluid of premature infants with intraventricular hemorrhage

Abstract: Intraventricular hemorrhage is a common cause of morbidity and mortality in premature infants. The rupture of the germinal zone into the ventricles entails loss of neural stem cells and disturbs the normal cytoarchitecture of the region, compromising late neurogliogenesis. Here we demonstrate that neural stem cells can be easily and robustly isolated from the hemorrhagic cerebrospinal fluid obtained during therapeutic neuroendoscopic lavage in preterm infants with severe intraventricular hemorrhage. Our analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…So far, most clinical trials have used fetal NSC (fNSC), but NSC from other sources such as pluripotent stem cells (PSC) are increasingly reaching the clinical stage. Furthermore, newer sources for primary NSC, such as the cerebrospinal fluid (CSF) of spina bifida or from premature infants with intracerebroventricular hemorrhage (ICVH) have been reported [ 4 , 5 , 6 , 7 ] and may become available in the near future ( Figure 1 ).…”
Section: Neural Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, most clinical trials have used fetal NSC (fNSC), but NSC from other sources such as pluripotent stem cells (PSC) are increasingly reaching the clinical stage. Furthermore, newer sources for primary NSC, such as the cerebrospinal fluid (CSF) of spina bifida or from premature infants with intracerebroventricular hemorrhage (ICVH) have been reported [ 4 , 5 , 6 , 7 ] and may become available in the near future ( Figure 1 ).…”
Section: Neural Stem Cellsmentioning
confidence: 99%
“…We and others have recently reported that primary NSC can be isolated from the CSF, collected for diagnostic or therapeutic purposes, of infants diagnosed with severe intracerebroventricular hemorrhage (IVH) or neural tube defects (NTD) [ 4 , 5 , 6 , 7 , 51 ].…”
Section: Neural Stem Cells From the Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The scarce numbers of adult NSCs or their aberrant alterations in neurodegenerative diseases suppose the lack of a reliable endogenous mechanism to replenish neurons in the event of their loss. Not in vain, stem cells offer the potential to reduce deleterious signaling and improve traumatic lesions [ 28 , 29 ], and also to slowdown the progression of devastating neurodegenerative diseases such as Huntington’s (HD) [ 30 , 31 ], Parkinson’s (PD) [ 32 , 33 ] or Alzheimer’s disease (AD) [ 34 , 35 , 36 ]. The idea of using stem cells to treat neurodegenerative diseases was proposed very long ago, obtaining valuable and abundant data using fetal human tissue [ 31 , 37 , 38 ] or induced pluripotent stem cells (IPSCs) [ 39 , 40 ].…”
Section: Introduction: Neural and Mesenchymal Stem Cells And Neurmentioning
confidence: 99%
“…However, these methods raise both safety and ethical concerns that are still under intense debate [ 41 , 42 , 43 , 44 , 45 , 46 ]. The main practical problems are the security, the very low yields of extraction, and the troublesome conditions of intervention on premature infants to harvest human NSCs [ 34 ]. Stem cells from the spinal cord of 8-week fetuses have been tested in clinical trials for chronic spinal cord injury [ 47 , 48 ].…”
Section: Introduction: Neural and Mesenchymal Stem Cells And Neurmentioning
confidence: 99%